Nutrient-Induced Changes of Liver Fat Content in Humans - Kovář, J; Poledne, R (Physiological research, 2025)
Metabolic-dysfunction associated steatotic liver disease (MASLD) affects approximately 30 % of the world adult population and even contributes to the increased mortality from cardiovascular disease. Dietary intervention, along with exercise, is the most important tool for the treatment of MASLD patients. Dietary composition can have profound effects on liver fat. This review summarizes the results of studies that used MR methods to study the effect of macronutrients on liver fat content. It focuses on intervention studies manipulating the content and quantity of macronutrients in long-term dietary intervention studies and, in more detail, on studies monitoring the effect of administered nutrients on changes in liver fat over several hours.
Keywords: živiny; Liver; Lipid Metabolism; ztučnělá játra; játra; Humans; Fatty Liver; Nutrients; metabolismus lipidů; lidé